Integrated Circuit Packaging, Assembly and Interconnections - Greig, William. (Springer US : Imprint: Springer, 2007)
Integrated Circuit Packaging, Assembly and Interconnections is intended as a multi-purpose text, serving individuals looking for an introduction, or a review, or an update of the various IC packaging, assembly, and interconnection technologies. To this end, it provides an overview of the materials and the processes, as well as the trends and available options that encompass electronic manufacturing. It covers both the technical issues and touches on some of the reliability concerns with the various technologies applicable to packaging and assembly of the IC. The focus is on the electronic manufacturing process which, in its simplest form, involves assembly of the IC into a package or interconnect substrate or board. The book discusses the various packaging approaches available, namely, single chip, multichip, and Chip On Board; the assembly options, chip & wire, tape automated bonding, and flip chip; and the essential high density package/substrate manufacturing technologies, thin film, thick film, cofired ceramic, and laminate printed wiring board (PWB) processes. Included also is a discussion of high density PWBs using build up/sequential processes. This material will provide a suitable knowledge-base essential for individuals who have the need or interest in understanding the basics of electronic manufacturing.